Malignant Transformation in Leukoplakia and its Associated Factors in Southern Iran: A Hospital Based Experience - Alireza BARFI QASRDASHTI; Mina Seied HABASHI; Peyman ARASTEH; Mahshid TORABI ARDAKANI; Zahra ABDOLI; Seyed Sajjad EGHBALI (Tehran University of Medical Sciences, 2017)
Background: We evaluated factors that affect malignant transformation of leukoplakia in a sample of the Iranian population. Methods: The records of patients with a clinical diagnosis of leukoplakia during a 20-year period from 1989-2009 referred to two of the largest referral centers in southern Iran were studied. Patients that developed malignant transformation were compared with patients that did not have malignant changes. Results: Of 522 patients, female patients, those over 50 yr old and with lesions located on the tongue had the highest rate of malignant changes. Female patients with malignant changes were mostly non-smokers (76.4%), while male patients with malignant changes were mostly smokers (63.8% in non-smokers) (P<0.001). In our univariate analysis, male sex and smoking showed lower chances for malignant transformation (OR: 0.57; CI=0.397-0.822 and OR: 0.025; CI=0.141-0.299, respectively), while age above 50 was a risk factor for malignant transformation (OR: 3.57; CI=2.32-5.42). In the multivariate analysis, smoking (OR: 0.317; 95% CI=0.16-0.626) and morphological presentation as erythroplakia (OR: 0.025; 95% CI=0.005-0.131) had low chances for developing malignant changes, while site of lesion on the tongue (OR: 774; 95% CI=60-9838) and morphological presentation as erythroleukoplakia (OR: 6.26; 95% CI=3.16-12.38) were a risk factor for developing malignant changes Conclusion: A follow-up program and further work-up should be considered for Iranian patients who have a leukoplakia lesion that is flat and are white patch or plaques with red components, in addition for patients who have lesions located on the tongue and for nonsmokers who develops leukoplakia lesions.